Accuracy of digital and conventional impressions in Fixed Implant Prosthesis - Freire, Julliana Cariry Palhano (2020)
Introduction: Accurate digital or conventional fingerprints are essential in the manufacture of Implant Fixed Prostheses, however there is no consensus in the literature on which technique is best clinically. Objectives: To analyze the conventional and digital printing techniques in Fixed Implant Prosthesis, such as the factors: bone loss, marginal fit, mold accuracy, clinical time and dental surgeon knowledge about the techniques. Methodology: A literature review was carried out through the search for scientific articles of the last 10 years, in the Pubmed database. Titles, abstracts and access to the full text were verified and the research selected according to the inclusion criteria. Results: Surveys indicate that there are no significant differences in bone loss, marginal fit, and mold accuracy relative to conventional and digital prints. However, professionals do not report technical preference and digital technology presents a procedure with shorter clinical time. Conclusion: The number of randomized clinical trials that test digital implant workflows on implants is low. The knowledge and clinical management of the dental surgeon influences the choice of available techniques.